The impact of SNP fingerprinting and parentage analysis on the effectiveness of variety recommendations in cacao - Padi, Francis K; Ofori, A.; Takrama, J.; Djan, E.; Opoku, S.Y.; Dadzie, A.M.; Bhattacharjee, Ranjana; Motamayor, J.; Zhang, D. (Springer, 2015)
Evidence for the impact of mislabeling and/or pollen contamination on consistency of field performance has been lacking to reinforce the need for strict adherence to quality control protocols in cacao seed garden and germplasm plot management. The present study used SNP fingerprinting at 64 loci to examine the diversity, labeling errors and parentage in 2551 trees obtained from six seed gardens, breeders clone collection and single-cross progenies and a sample of farmers’ trees in Ghana. Clone mislabeling was pervasive, both within the seed garden clones and among clones of the breeders’ active collection. Among the seed garden clones, mislabeled trees were assigned to other parental clones used in the seed garden, pointing to labeling errors prior to planting as the principal cause of mislabeling. Among the breeders’ clone collection, both homonymous and synonymous mislabeling were identified in addition to trees with unique genotypes. This implicates pre-planting labeling errors and rootstocks overtaking budded scions. Parentage analysis supported the Amelonado ancestry of farmers’ varieties but with significant contribution of Upper Amazon introductions. Parentage of recently developed clones and of progenies of controlled crosses showed evidence of both pollen contamination and effects of mislabeled parents. The observed patterns of unexpected parentage had direct effects on the consistency of the variety performance between trials and increased within-plot variability for families with mixed ancestry. The results provide a strong basis for mainstreaming SNP fingerprinting in cacao breeding programs to improve the efficiency of the variety development process.Evidence for the impact of mislabeling and/or pollen contamination on consistency of field performance has been lacking to reinforce the need for strict adherence to quality control protocols in cacao seed garden and germplasm plot management. The present study used SNP fingerprinting at 64 loci to examine the diversity, labeling errors and parentage in 2551 trees obtained from six seed gardens, breeders clone collection and single-cross progenies and a sample of farmers’ trees in Ghana. Clone mislabeling was pervasive, both within the seed garden clones and among clones of the breeders’ active collection. Among the seed garden clones, mislabeled trees were assigned to other parental clones used in the seed garden, pointing to labeling errors prior to planting as the principal cause of mislabeling. Among the breeders’ clone collection, both homonymous and synonymous mislabeling were identified in addition to trees with unique genotypes. This implicates pre-planting labeling errors and rootstocks overtaking budded scions. Parentage analysis supported the Amelonado ancestry of farmers’ varieties but with significant contribution of Upper Amazon introductions. Parentage of recently developed clones and of progenies of controlled crosses showed evidence of both pollen contamination and effects of mislabeled parents. The observed patterns of unexpected parentage had direct effects on the consistency of the variety performance between trials and increased within-plot variability for families with mixed ancestry. The results provide a strong basis for mainstreaming SNP fingerprinting in cacao breeding programs to improve the efficiency of the variety development process.Evidence for the impact of mislabeling and/or pollen contamination on consistency of field performance has been lacking to reinforce the need for strict adherence to quality control protocols in cacao seed garden and germplasm plot management. The present study used SNP fingerprinting at 64 loci to examine the diversity, labeling errors and parentage in 2551 trees obtained from six seed gardens, breeders clone collection and single-cross progenies and a sample of farmers’ trees in Ghana. Clone mislabeling was pervasive, both within the seed garden clones and among clones of the breeders’ active collection. Among the seed garden clones, mislabeled trees were assigned to other parental clones used in the seed garden, pointing to labeling errors prior to planting as the principal cause of mislabeling. Among the breeders’ clone collection, both homonymous and synonymous mislabeling were identified in addition to trees with unique genotypes. This implicates pre-planting labeling errors and rootstocks overtaking budded scions. Parentage analysis supported the Amelonado ancestry of farmers’ varieties but with significant contribution of Upper Amazon introductions. Parentage of recently developed clones and of progenies of controlled crosses showed evidence of both pollen contamination and effects of mislabeled parents. The observed patterns of unexpected parentage had direct effects on the consistency of the variety performance between trials and increased within-plot variability for families with mixed ancestry. The results provide a strong basis for mainstreaming SNP fingerprinting in cacao breeding programs to improve the efficiency of the variety development process.